Recent Advances on Early-Stage Fire-Warning Systems: Mechanism, Performance, and Perspective - Li, Xiaolu; Vázquez‑López, Antonio; Saeza, José Sánchez del Río; Wang, De‑Yi (Nano-Micro Letters, 2022)
Early-stage fire-warning systems (EFWSs) have attracted significant attention owing to their superiority in detecting fire situations occurring in the pre-combustion process. Substantial progress on EFWSs has been achieved recently, and they have presented a considerable possibility for more evacuation time to control constant unintentional fire hazards in our daily life. This review mainly makes a comprehensive summary of the current EFWSs, including the working mechanisms and their performance. According to the different working mechanisms, fire alarms can be classified into graphene oxide-based fire alarms, semiconductor-based fire alarms, thermoelectric-based fire alarms, and fire alarms on other working mechanisms. Finally, the challenge and prospect for EFWSs are briefly provided by comparing the art of state of fire alarms. This work can propose a more comprehensive understanding of EFWSs and a guideline for the cutting-edge development direction of EFWSs for readers. Highlights: 1 Thermosensitive fire alarms with various working mechanisms are overviewed. 2 Different calculation methods for response time are discussed. 3 Warning signal conversion types are provided. 4 Limitations, challenges, and development direction are put forward.